Stable operating limits and improvement methods for hydropower and photovoltaic integration through MMC-HVDC systems - Peng, Maolan; Feng, Lei; Zhang, Shuwen; Zhao, Wei (Frontiers in Electronics, 2024)
This paper addresses the critical need to determine the stable operating limit of modular multilevel converter-based high voltage direct current (MMC-HVDC) systems, particularly concerning the integration of extensive renewable energy sources. To achieve this, the steady-state mathematical model and state-space model of bundled hydropower and photovoltaic integration through MMC-HVDC systems are established. A novel methodology considering steady-state and small-signal stability constraints is proposed to compute the stable operating region of the system. The quantitative assessment reveals that diminishing AC system short-circuit capacities amplify restrictions from small-signal stability constraints, thereby reducing the system's stable operating region. Eigenvalue and participation factor analyses shed light on the pivotal factors affecting small-signal stability in weak AC systems. To expand the system's stable operating region, a supplementary frequency damping control strategy is proposed. The theoretical analysis and calculation results are validated by building a simulation model for the bundled hydropower and photovoltaic integration through MMC-HVDC systems in PSCAD/EMTDC.